Yield of Fine Rice Varieties as Influenced by Integrated Management of Poultry Manure Urea Super Granules and Prilled Urea (Journal of Environmental Science and Natural Resources, 2012)
Higher grain yield (2.45 t ha-1) was obtained in BRRI dhan34 than that of Kalizira (2.23 t ha-1). Fertilizer application @ 1.8g USG and other inorganic fertilizer ( full dose for T. aman + PM at 3.5 tha-1) gave the highest grain yield (2.85 t ha-1) and lowest grain yield (1.52 t ha-1) was found at control (no PM and NPKS). Grain yields were affected by the interaction of variety and nutrient management. The highest grain yield (2.88 t ha-1) was found in BRRI dhan34 coupled with 1.8g USG and other inorganic fertilizer(full dose for T. aman) + PM at 3.5 t ha-1 and the lowest grain yield (1.24 t ha-1) was found in Kalizira coupled with control (no PM and NPKS). The combination of fine rice BRRI dhan34 and 1.8g USG and other inorganic fertilizer (full dose for T. aman) + PM at 3.5t ha-1 appeared as the best treatment combination for the highest grain yield. DOI: http://dx.doi.org/10.3329/jesnr.v5i1.11567 J. Environ. Sci. & Natural Resources, 5(1): 129 - 132, 2012